2020
DOI: 10.3390/ijms21249577
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PPAR Ligands as Modulators of Resolution of Inflammation, via Their Influence on Cytokines and Oxylipins Release in Astrocytes

Abstract: Neuroinflammation is a key process of many neurodegenerative diseases and other brain disturbances, and astrocytes play an essential role in neuroinflammation. Therefore, the regulation of astrocyte responses for inflammatory stimuli, using small molecules, is a potential therapeutic strategy. We investigated the potency of peroxisome proliferator-activated receptor (PPAR) ligands to modulate the stimulating effect of lipopolysaccharide (LPS) in the primary rat astrocytes on (1) polyunsaturated fatty acid (PUF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 73 publications
(57 reference statements)
0
17
0
Order By: Relevance
“…To identify the difference between lipid fractions, we analyzed them using the approach we developed previously with the mass-spectrometric method of oxylipin profiles detection [ 35 , 36 ]. We obtained oxylipin profiles from astrocytes treated solely with LPS, ML355, and Zileuton or in combinations for 24 h ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
“…To identify the difference between lipid fractions, we analyzed them using the approach we developed previously with the mass-spectrometric method of oxylipin profiles detection [ 35 , 36 ]. We obtained oxylipin profiles from astrocytes treated solely with LPS, ML355, and Zileuton or in combinations for 24 h ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence that treatment with the ligand (WY14643) of peroxisome-proliferator-activated receptor alpha facilitates the expression of anti-inflammatory cytokine interleukin-10 mRNA in rats [ 67 ]. The peroxisome-proliferator-activated receptor beta agonist (GW501516) and the peroxisome-proliferator-activated receptor gamma agonist (rosiglitazone) elicit the interleukin-10 release [ 68 ]. Besides upregulating M2 polarization-related factor interleukin-10, the use of peroxisome-proliferator-activated receptor gamma agonists also can downregulate macrophage M1 polarization-related factors such as interleukin-1 and interleukin-6 [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rice bran extract (which is rich in PUFA) as well as pioglitazone have been reported to protect against inflammation induced by lipopolysaccharides (LPS) in a mouse model, decreasing TNF-a and COX2 levels in brain, reducing striatal plaque formation and suppressing cortical and hippocampal tissue damage, all effects requiring PPARγ activity [60]. Other recent studies converged to support positive, PPARγ-dependent, role against neuroinflammation of PPARγ agonists as rosiglitazone which induced IL-10 in primary rat astrocytes exposed to LPS [61], or pioglitazone in a rat model of chronic intermittent hypoxia [62]. Other studies did not assess PPARγ involvement but still reported a protective role of its agonists against neuroinflammation, as rosiglitazone in a mouse model of epilepsy [63] and pioglitazone in rat models of autism [64], Parkinson's disease [65], or neuroinflammation due to intracerebroventricular administration of LPS [66].…”
Section: Neuroinflammationmentioning
confidence: 99%